Benzoxazine-epoxy resin glue solution, copper-clad plate and preparation method
By using modified benzoxazine-epoxy resin glue in copper clad plate, the insufficient performance of halogen-free flame-retardant copper clad plate is solved, and high flame retardancy, heat resistance and mechanical properties are improved, while reducing dielectric loss.
Patent Information
- Application Number
- CN202411489864.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-25
AI Technical Summary
The existing halogen-free flame-retardant copper clad plate has poor flame retardant performance, and its heat resistance and mechanical properties have decreased. At the same time, the dielectric constant of benzoxazine resin is insufficient, which cannot meet the requirements of high frequency and high speed.
The benzoxazine-epoxy resin glue is used to improve the flame retardant epoxy resin, aromatic backbone benzoxazine and fat backbone benzoxazine, and the flame retardant, thermal and processing properties of the material, and eliminate internal stress during the curing process to reduce defects.
The flame retardancy, heat resistance and mechanical properties of the copper clad plate are significantly improved, dielectric loss is reduced, glass transition temperature and thermal layering time are improved, and the overall performance of the material is enhanced.
Smart Images

Figure BDA0005099721910000091 
Figure BDA0005099721910000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper clad laminates, and in particular to a benzoxazine-epoxy resin adhesive, a copper clad laminate and a preparation method thereof. Background Art
[0002] During the use of electronic equipment, the printed circuit boards contained therein often have hidden dangers of fire and other safety crises due to the accumulation of heat. In order to prevent this from happening, very high requirements are placed on the flame retardant properties of the circuit boards. As the basic material in the production process of printed circuit boards, the improvement of the flame retardant properties of copper clad laminates is of great significance to the improvement of the flame retardant properties of circuit boards. In the preparation process of flame-retardant copper clad laminates, flame retardant compounds containing halogens or antimony elements that are harmful to the environment are often introduced to improve the flame retardancy of the board. However, with the enhancement of people's awareness of environmental protection, the demand for halogen-free flame-retardant copper clad laminates is increasing. However, in order to take into account the flame retardant properties, the heat resistance and mechanical properties, including toughness and strength, of the commonly used halogen-free flame-retardant copper clad laminates on the market are lower than those of general halogen flame-retardant copper clad laminates.
[0003] Entering the 21st century represented by cloud computing, the Internet of Things and big data, with the development of a new generation of high-density and high-speed integrated circuits, there is an urgent need to design and develop low-dielectric thermosetting resins. As a result, the application of benzoxazine resins in the field of a new generation of high-frequency and high-speed integrated circuits, especially in microwave communication systems, has attracted widespread attention. Benzoxazine resins have many unique properties, such as good mechanical properties, high carbon residue rate, volume shrinkage / expansion close to zero during polymerization, low water absorption, good chemical resistance and UV resistance, and even high glass transition temperature at a low crosslinking density. In particular, its good dielectric properties, especially its relatively low and stable dielectric constant (Dk) at high frequencies, make benzoxazine resins have good application prospects in the next generation of microelectronics industry. However, the dielectric constant of general benzoxazine resins is generally around 3.5, which cannot meet the requirements of high frequency and high speed. Therefore, low-dielectric modification of benzoxazine resins is a very worthy theoretical and application topic, which has very important social value and theoretical significance. Summary of the invention
[0004] In order to solve the above-mentioned technical problems existing in the prior art, the present invention provides a benzoxazine-epoxy resin adhesive, a copper clad laminate and a preparation method to solve the problems of poor flame retardancy, reduced heat resistance and mechanical properties of the halogen-free flame retardant copper clad laminate, as well as the technical problem of low dielectric modification of benzoxazine.
[0005] The technical solution of the present invention to solve the above technical problems is as follows:
[0006] The first aspect of the present invention is to provide a benzoxazine-epoxy resin adhesive, which comprises the following components, measured by mass: 80-120 parts of a modified flame retardant epoxy resin, 20-40 parts of an aromatic main chain benzoxazine, 20-40 parts of an aliphatic main chain benzoxazine, 20-40 parts of a metal hydroxide, 0.4-0.6 parts of a curing agent, and 70-80 parts of a composite solvent.
[0007] On the basis of the above technical solution, the present invention can also make the following improvements:
[0008] Furthermore, the aromatic main chain benzoxazine is prepared by a solution method using bisphenol A, polyformaldehyde, 4,4'-diaminodiphenylmethane and aniline as raw materials; wherein the mass ratio of bisphenol A, 4,4'-diaminodiphenylmethane and polyformaldehyde is 1:0.5-2:1-3, preferably 1:1:2.
[0009] After dissolving bisphenol A, aniline, 4,4'-diaminodiphenylmethane and polyformaldehyde in a solvent, reflux in a flask equipped with a condenser to remove the initial reactants and the soluble part, precipitate a yellow transparent liquid with methanol, and dry it in a vacuum oven at a temperature of 55°C for 12-16 hours to obtain an aromatic main chain benzoxazine.
[0010] Furthermore, the fatty main chain benzoxazine is prepared by a solution method using 1,6-hexanediamine, aniline, bisphenol A and paraformaldehyde as raw materials; wherein the mass ratio of bisphenol A, aniline and paraformaldehyde is 1:0.5-2:1-3, preferably 1:1:2.
[0011] After dissolving bisphenol A, aniline, 1,6-hexanediamine and polyformaldehyde in a solvent, reflux in a flask equipped with a condenser to remove the initial reactants and the soluble part, precipitate a white transparent liquid with methanol, and dry it in a vacuum oven at a temperature of 55°C for 12-16 hours to obtain a fatty main chain benzoxazine.
[0012] Furthermore, the modified flame-retardant epoxy resin is prepared by epoxy resin and hydroxy carbon nanotubes (MWCNTs-OH).
[0013] Further, the preparation of the modified flame retardant epoxy resin comprises the following steps:
[0014] (1) taking hydroxy carbon nanotubes and sodium dodecylbenzene sulfonate in a mass ratio of 1:0.03-0.2 and adding 250-350 parts of alcohol, heating to 50-60° C., stirring and dispersing to obtain solution A;
[0015] (2) adding acetone to solution A, stirring and dispersing, to obtain solution B, wherein the concentration of hydroxy carbon nanotubes is 0.20 wt % to 0.30 wt %;
[0016] (3) Weigh 100-150 parts of epoxy resin and dissolve it in 200-220 parts of acetone. Then add it to solution B, stir it evenly at room temperature, raise the temperature to 70° C., and stir it evenly again to obtain a modified flame-retardant epoxy resin.
[0017] The mass ratio of the hydroxy carbon nanotubes to sodium dodecylbenzene sulfonate is preferably 1:0.08.
[0018] Hydroxyl carbon nanotubes (MWCNTs-OH) are prepared by in-situ polymerization process, epoxy resin is used as the main material, and then the hydroxyl carbon nanotubes (MWCNTs-OH) are added to the epoxy resin to prepare a highly flame-retardant epoxy resin material. The hydroxyl carbon nanotubes and the epoxy resin are any one available on the market.
[0019] The epoxy resin is preferably a bisphenol A epoxy resin, the metal hydroxide includes one or a combination of two of magnesium hydroxide and aluminum hydroxide, the composite solvent is a mixed solution of acetone, butanone and toluene in a mass ratio of 1: (0.6-1): (0.8-1.2), and the curing agent includes one or a combination of several of 1,2,4,6-tris(dimethylaminomethyl)phenol, benzyldimethylamine, triethylamine, triethanolamine and o-hydroxybenzyldimethylamine.
[0020] The second aspect of the present invention is to provide a method for preparing the above-mentioned benzoxazine-epoxy resin glue, comprising the following steps: mixing a modified flame-retardant epoxy resin, an aromatic main chain benzoxazine and an aliphatic main chain benzoxazine, adding a composite solvent, stirring and mixing for 10-20 minutes, adding a curing agent, raising the temperature to 80-90°C and continuing to stir and react for 2-3 hours, then adding a metal hydroxide, and stirring for 2-3 hours to obtain the benzoxazine-epoxy resin glue.
[0021] The third aspect of the present invention is to provide a copper clad laminate prepared by using the above-mentioned benzoxazine-epoxy resin glue.
[0022] Another aspect of the present invention is to provide a method for preparing the copper clad laminate, comprising the following steps:
[0023] S1, impregnating glass fiber cloth with benzoxazine-epoxy resin glue, and then performing semi-curing treatment, wherein the semi-curing treatment temperature is 140-180° C., and the time is 6-8 hours to obtain a semi-cured sheet;
[0024] S2. The semi-cured sheet and the copper foil covering both sides thereof are stacked together, and a copper clad laminate is obtained through a lamination process.
[0025] Furthermore, in S1, the thickness of the prepreg is 1-10 mm; and in S2, the number of prepregs is 2-8.
[0026] Furthermore, in S2, the lamination process conditions are: pressure of 0.6-1 MPa, temperature of 180-220° C., and time of 2-8 h.
[0027] Compared with the prior art, the present invention has the following technical effects:
[0028] The benzoxazine-epoxy resin glue provided by the present invention increases Tg and reduces dielectric loss by adding aromatic main chain benzoxazine, and improves the processing performance and thermal performance of the material by adding aliphatic main chain benzoxazine. The addition of modified flame-retardant epoxy resin can significantly improve the flame retardancy of the epoxy resin itself, and in the process of promoting the curing of the epoxy resin, no byproduct small molecules are generated, no obvious volume change occurs, and the residual stress inside the epoxy resin after curing can be eliminated, and the generation of defects is reduced, thereby improving the mechanical properties of the finally prepared copper clad laminate.
[0029] The benzoxazine-epoxy resin glue contains a large number of benzene ring structures, and the material has high rigidity and enhanced heat resistance, which is manifested in that the copper clad laminate prepared with the benzoxazine-epoxy resin glue has high strength and good thermal stability. The addition of aromatic main chain benzoxazine and aliphatic main chain benzoxazine improves the processing performance and thermal performance of the material, and improves the electrical performance to a certain extent;
[0030] At the same time, metal hydroxides and composite solvents are added to the benzoxazine-epoxy resin adhesive system. Compared with other similar inorganic flame retardants, metal hydroxides not only have excellent synergistic effects on the flame retardant effect of benzoxazine resin, but also can inhibit the generation of smoke and harmful gases. It has the triple effects of flame retardancy, smoke suppression and filling in the system. DETAILED DESCRIPTION
[0031] The following specific embodiments illustrate the implementation of the present invention, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Although the description of the present invention will be introduced in conjunction with the preferred embodiment, this does not mean that the features of this invention are limited to this implementation. On the contrary, the purpose of introducing the invention in conjunction with the implementation is to cover other options or modifications that may extend based on the claims of the present invention. In order to provide a deep understanding of the present invention, the following description will include many specific details. The present invention can also be implemented without using these details. In addition, in order to avoid confusion or blurring the focus of the present invention, some specific details will be omitted in the description. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0032] Example 1
[0033] 1. Preparation of aromatic main chain benzoxazines
[0034] Prepare 10 parts of bisphenol A, 10 parts of 4,4'-diaminodiphenylmethane, and 20 parts of polyformaldehyde, dissolve bisphenol A, 4,4'-diaminodiphenylmethane, and polyformaldehyde in toluene, reflux in a flask equipped with a condenser to remove the initial reactants and the soluble part, precipitate a yellow transparent liquid with methanol, and dry it in a vacuum oven at a temperature of 55°C for 12 hours to obtain an aromatic main chain benzoxazine.
[0035] 2. Preparation of fatty main chain benzoxazines
[0036] Prepare 10 parts of bisphenol A, 10 parts of aniline and 20 parts of polyformaldehyde, dissolve bisphenol A, aniline and polyformaldehyde in toluene, reflux in a flask equipped with a condenser to remove the initial reactants and the soluble part, precipitate the white transparent liquid with methanol, and dry it in a vacuum oven at a temperature of 55°C for 12 hours to obtain a fatty main chain benzoxazine.
[0037] 3. Preparation of modified flame retardant epoxy resin
[0038] (1) Pretreatment of hydroxylated carbon nanotubes (MWCNTs-OH)
[0039] In parts by weight, 100 parts of MWCNTs-OH and 8 parts of sodium dodecylbenzene sulfonate (SDBS) were taken and mixed with 250 parts of alcohol; the mixture was heated to 50° C. and stirred for 60 minutes until the mixture was evenly dispersed, thereby obtaining solution A;
[0040] (2) Further treatment of hydroxylated carbon nanotubes (MWCNTs-OH)
[0041] Acetone was added to solution A to prepare a solution with a concentration of 0.25 wt% of MWCNTs-OH. The solution was stirred and dispersed for 60 min at room temperature until the solution was uniformly dispersed to obtain solution B.
[0042] (3) Treatment of dissolved epoxy resin
[0043] Weigh 100 parts of epoxy resin and dissolve it in 200 parts of acetone, then add it to solution B, stir at room temperature for 2 hours, then heat it to 70°C, stir it for 5 hours, and then stir it at room temperature for another 5 hours until it is evenly stirred to obtain a flame-retardant epoxy resin.
[0044] 4. Preparation of benzoxazine-epoxy resin glue
[0045] The components are: 80 parts of modified flame retardant epoxy resin, 20 parts of aromatic main chain benzoxazine, 20 parts of aliphatic main chain benzoxazine, 20 parts of magnesium hydroxide, 0.4 parts of triethylamine, and 70 parts of composite solvent (28 parts of acetone, 16.8 parts of butanone and 25.2 parts of toluene);
[0046] The modified flame-retardant epoxy resin, aromatic main-chain benzoxazine and aliphatic main-chain benzoxazine were mixed and then added with a composite solvent. After stirring for 10 minutes, triethylamine was added, the temperature was raised to 80°C and the stirring reaction was continued for 2 hours. Then, magnesium hydroxide was added and stirred for another 2 hours to obtain a benzoxazine-epoxy resin glue.
[0047] 5. Preparation of copper clad laminate
[0048] S1. impregnating glass fiber cloth (model 7628 glass fiber cloth) with benzoxazine-epoxy resin glue, and then semi-curing treatment, wherein the semi-curing process is first cured at a temperature of 140° C. for 2 hours, then raised to 160° C. for curing for 2 hours, and then raised to 180° C. for curing for 2 hours to obtain a semi-cured sheet;
[0049] S2. Take 2 prepregs, cut and stack them, and place a copper foil on the upper and lower parts of the prepregs, press them at a pressure of 0.6 MPa and a temperature of 220°C, and then post-process them to obtain a benzoxazine resin-based halogen-free flame-retardant FR-4 copper clad laminate; the post-processing process is specifically: the temperature is 200°C and the processing time is 2h.
[0050] Example 2
[0051] Step 1, step 2, and step 3 are the same as those in Example 1.
[0052] 4. Preparation of benzoxazine-epoxy resin glue
[0053] The components are: 100 parts of modified flame retardant epoxy resin, 30 parts of aromatic main chain benzoxazine, 30 parts of aliphatic main chain benzoxazine, 30 parts of aluminum hydroxide, 0.5 parts of triethanolamine, and 75 parts of composite solvent (25 parts of acetone, 25 parts of butanone and 25 parts of toluene);
[0054] The modified flame-retardant epoxy resin, aromatic main-chain benzoxazine and aliphatic main-chain benzoxazine were mixed and then added with a composite solvent. After stirring for 15 minutes, triethanolamine was added, the temperature was raised to 85°C and the stirring reaction was continued for 2.5 hours. Then, aluminum hydroxide was added and stirred for another 2.5 hours to obtain a benzoxazine-epoxy resin glue.
[0055] 5. Same as step 5 in Example 1.
[0056] Example 3
[0057] Step 1, step 2, and step 3 are the same as those in Example 1.
[0058] 4. Preparation of benzoxazine-epoxy resin glue
[0059] The components are: 120 parts of modified flame retardant epoxy resin, 40 parts of aromatic main chain benzoxazine, 40 parts of aliphatic main chain benzoxazine, 40 parts of metal hydroxide (20 parts of magnesium hydroxide, 20 parts of aluminum hydroxide), 0.6 parts of benzyldimethylamine, and 80 parts of composite solvent (25 parts of acetone, 25 parts of butanone and 30 parts of toluene);
[0060] The modified flame-retardant epoxy resin, aromatic main-chain benzoxazine and aliphatic main-chain benzoxazine are mixed and then a composite solvent is added. After stirring for 20 minutes, benzyldimethylamine is added, the temperature is raised to 90°C and the stirring reaction is continued for 3 hours, and then a metal hydroxide is added and stirred for another 3 hours to obtain a benzoxazine-epoxy resin glue.
[0061] 5. Same as step 5 in Example 1.
[0062] Comparative Example 1
[0063] The difference between Comparative Example 1 and Example 1 is that the modified flame-retardant epoxy resin in Example 1 is replaced with ordinary epoxy resin.
[0064] The specific steps are as follows: Step 1 and Step 2 are the same as in Example 1.
[0065] 3. Preparation of benzoxazine-epoxy resin glue
[0066] The components are: 80 parts of ordinary epoxy resin, 20 parts of aromatic main chain benzoxazine, 20 parts of aliphatic main chain benzoxazine, 20 parts of magnesium hydroxide, 0.4 parts of triethylamine, and 70 parts of composite solvent (28 parts of acetone, 16.8 parts of butanone and 25.2 parts of toluene);
[0067] Ordinary epoxy resin, aromatic main chain benzoxazine and aliphatic main chain benzoxazine are mixed and then a composite solvent is added. After stirring for 10 minutes, triethylamine is added, the temperature is raised to 80°C and the stirring reaction is continued for 2 hours. Then magnesium hydroxide is added and the mixture is stirred for another 2 hours to obtain benzoxazine-epoxy resin glue.
[0068] 4. Preparation of copper clad laminate
[0069] S1. impregnating the prepared benzoxazine-epoxy resin impregnation glue into glass fiber cloth (model 7628 glass fiber cloth), and then semi-curing treatment, wherein the semi-curing process is first cured at a temperature of 140° C. for 2 hours, then the temperature is increased to 160° C., cured for 2 hours, and then the temperature is increased again to 180° C., cured for 2 hours, to obtain a semi-cured sheet;
[0070] S2. Take two prepregs, cut and stack them, and place a copper foil on the upper and lower sides of the prepregs, press them at a pressure of 0.6 MPa and a temperature of 180° C., and then post-process to obtain a benzoxazine resin-based halogen-free flame-retardant FR-4 copper clad laminate.
[0071] Comparative Example 2
[0072] The difference between Comparative Example 2 and Example 2 is that all modified benzoxazine resins (aromatic main chain benzoxazine and aliphatic main chain benzoxazine) are replaced with ordinary benzoxazine resins, and the modified flame retardant epoxy resin is replaced with ordinary epoxy resin.
[0073] 1. Preparation of benzoxazine-epoxy resin glue
[0074] The components are: 100 parts of ordinary epoxy resin, 90 parts of ordinary benzoxazine resin, 30 parts of aluminum hydroxide, 0.5 parts of triethanolamine, and 75 parts of composite solvent (25 parts of acetone, 25 parts of butanone and 25 parts of toluene);
[0075] Ordinary epoxy resin and ordinary benzoxazine resin were mixed and then added with the composite solvent. After stirring for 15 minutes, triethanolamine was added, the temperature was raised to 85°C and the stirring reaction was continued for 2.5 hours. Then aluminum hydroxide was added and stirred for another 2.5 hours to obtain benzoxazine-epoxy resin glue.
[0076] 2. Same as step 4 in Comparative Example 1.
[0077] Comparative Example 3
[0078] The difference between Comparative Example 3 and Example 3 is that all modified benzoxazine resins are replaced with ordinary benzoxazine, and the modified epoxy resin is also replaced with ordinary epoxy resin.
[0079] 1. Preparation of benzoxazine-epoxy resin glue
[0080] The components are: 120 parts of ordinary epoxy resin, 140 parts of ordinary benzoxazine, 40 parts of metal hydroxide (20 parts of magnesium hydroxide, 20 parts of aluminum hydroxide), 0.6 parts of benzyldimethylamine, and 80 parts of composite solvent (25 parts of acetone, 25 parts of butanone and 30 parts of toluene);
[0081] Ordinary epoxy resin and ordinary benzoxazine are mixed and then added with a composite solvent. After stirring for 20 minutes, benzyldimethylamine is added, the temperature is raised to 90°C and the stirring reaction is continued for 3 hours. Then, a metal hydroxide is added and the stirring is continued for another 3 hours to obtain a benzoxazine-epoxy resin glue.
[0082] 2. Same as step 4 in comparative example 1.
[0083] Performance testing standards
[0084] 1. Thermal stability test: The glass transition temperature of the prepregs obtained in the examples and comparative examples was tested using differential scanning calorimetry.
[0085] 2. Peel strength test: According to IPC-TM-650 2.4.8.1 "Peel Strength and Metal Foil (Benchmark Target Hole for Thin Plate)", the peel strength of the benzoxazine resin-based halogen-free flame-retardant FR-4 copper clad laminate obtained in the embodiment and the comparative example was tested.
[0086] 3. Flame retardant performance test: According to the UL94 safety standard "Flammability test of plastic materials in equipment and appliances", the flame retardant properties of the benzoxazine resin-based halogen-free flame retardant FR-4 copper clad laminates obtained in the examples and comparative examples were tested.
[0087] 4. Electrical performance test: According to the relevant records in GJB 1651A-2017 "Test methods for metal foil-clad laminates for printed circuits", the breakdown voltage of the benzoxazine resin-based halogen-free flame-retardant FR-4 copper-clad laminates obtained in the examples and comparative examples was tested.
[0088] Performance testing equipment
[0089] Experimental results: The performance comparison data of the copper clad laminates prepared in Examples 1-3 and Comparative Examples 1-3 are shown in Table 1. The test of glass transition temperature (DCS) was measured by a differential scanner of TA Instruments Waters, USA; the test of T288 thermal delamination time and thermal expansion coefficient CTE (50-260°C, Z axis) was measured by a thermomechanical analyzer of TA Instruments Waters, USA; the dielectric constant Dk (10GHz), dielectric constant Df (10GHz), dielectric constant Dk (5GHz), and dielectric constant Df (5GHz) were measured by a network analyzer of KEYS I GHT, USA.
[0090] Table 1 Statistical table of experimental test results of Examples 1-3 and Comparative Examples 1-3
[0091]
[0092]
[0093] The results in the above table show that in the application of the resin composition obtained by the present invention in the copper clad laminate, it can be seen through comparative analysis that the addition of the modified flame retardant epoxy resin plays an important role in the flame retardancy of the system and also improves the heat resistance to a certain extent; by comparing and analyzing the experimental results of Examples 1-3 and Comparative Examples 2-3, it can be seen that the combined addition of the modified flame retardant epoxy resin and the modified benzoxazine resin improves the thermal stratification time and various properties while improving the TG and electrical properties. It can be seen that the composite addition of the two plays a certain role in increasing the glass transition temperature of the resin glue, increasing the thermal decomposition time, increasing the heat resistance time, and reducing the thermal expansion coefficient.
[0094] The benzoxazine-epoxy resin adhesive provided by the present invention can significantly improve the flame retardancy of the epoxy resin itself by adding a modified flame retardant epoxy resin, and in the process of promoting the curing of the epoxy resin, no byproduct small molecules are generated, no obvious volume change occurs, and the residual stress inside the epoxy resin after curing can be eliminated, and the generation of defects is reduced, thereby improving the mechanical properties of the obtained copper clad laminate; the electrical properties of the benzoxazine are improved by adding aromatic main chain benzoxazine and aliphatic main chain benzoxazine, and then the benzoxazine is blended with the modified flame retardant epoxy resin to prepare a resin adhesive, thereby solving the defects of the epoxy resin, improving the glass transition temperature of the resin adhesive, and improving the flame retardancy of the composite material, so that no flame retardant needs to be added when the composite material is used to form the resin adhesive; the copper clad laminate prepared by the adhesive can effectively reduce the byproduct small molecules generated by combustion, and at the same time can reduce the dielectric constant and dielectric loss of the copper clad laminate, and improve the heat resistance and Tg.
[0095] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A benzoxazine-epoxy resin glue, characterized in that: The invention comprises the following components by weight: 80-120 parts of modified flame retardant epoxy resin, 20-40 parts of aromatic main chain benzoxazine, 20-40 parts of aliphatic main chain benzoxazine, 20-40 parts of metal hydroxide, 0.4-0.6 parts of curing agent and 70-80 parts of composite solvent.
2. The benzoxazine-epoxy resin glue according to claim 1, characterized in that: The aromatic main chain benzoxazine is prepared by a solution method using bisphenol A, polyformaldehyde, 4,4'-diaminodiphenylmethane and aniline as raw materials; wherein the mass ratio of bisphenol A, 4,4'-diaminodiphenylmethane and polyformaldehyde is 1:0.5-2:1-3.
3. The benzoxazine-epoxy resin glue according to claim 1, characterized in that: The fatty main chain benzoxazine is prepared by a solution method using 1,6-hexanediamine, aniline, bisphenol A and paraformaldehyde as raw materials; wherein the mass ratio of bisphenol A, aniline and paraformaldehyde is 1:0.5-2:1-3.
4. The benzoxazine-epoxy resin glue according to claim 1, characterized in that: The modified flame-retardant epoxy resin is prepared by reacting epoxy resin with hydroxy carbon nanotubes (MWCNTs-OH).
5. The benzoxazine-epoxy resin adhesive according to claim 4, characterized in that: The preparation of the modified flame retardant epoxy resin comprises the following steps: (1) taking hydroxy carbon nanotubes and sodium dodecylbenzene sulfonate in a mass ratio of 1:0.03-0.2, adding alcohol and mixing, heating to 50-60° C., stirring and dispersing, and obtaining solution A; (2) adding acetone to solution A, stirring and dispersing, to obtain solution B, wherein the concentration of hydroxy carbon nanotubes is 0.20 wt % to 0.30 wt %; (3) Weigh 100-150 parts of epoxy resin and dissolve it in 200-220 parts of acetone. Then add it to solution B, stir it evenly at room temperature, raise the temperature to 70° C., and stir it evenly again to obtain a modified flame-retardant epoxy resin.
6. A method for preparing the benzoxazine-epoxy resin adhesive according to any one of claims 1 to 5, characterized in that: The following steps are involved: The modified flame-retardant epoxy resin, aromatic main-chain benzoxazine and aliphatic main-chain benzoxazine are mixed, and then a composite solvent is added. After stirring for 10-20 minutes, a curing agent is added, the temperature is increased to 80-90° C. and the stirring reaction is continued for 2-3 hours. Then, a metal hydroxide is added, and the stirring is continued for 2-3 hours to obtain a benzoxazine-epoxy resin glue.
7. A copper clad laminate, characterized in that: The method is prepared by using the benzoxazine-epoxy resin adhesive according to any one of claims 1 to 5.
8. A method for preparing the copper clad laminate according to claim 7, characterized in that: The following steps are involved: S1, impregnating glass fiber cloth with benzoxazine-epoxy resin glue, and then performing semi-curing treatment, wherein the semi-curing treatment temperature is 140-180° C., and the time is 6-8 hours to obtain a semi-cured sheet; S2. The semi-cured sheet and the copper foil covering both sides thereof are stacked together, and a copper clad laminate is obtained through a lamination process.
9. The method for preparing a copper clad laminate according to claim 8, characterized in that: In S1, the thickness of the prepreg is 1-10 mm; in S2, the number of prepregs is 2-8.
10. The method for preparing a copper clad laminate according to claim 8, characterized in that: In S2, the lamination process conditions are: pressure of 0.6-1 MPa, temperature of 180-220°C, and time of 2-8 h.
Citation Information
Cited By
Copper-clad plate based on polyphenyl ether resin glue solution and preparation process of copper-clad plate
CN120059443A